Alone in the Crowd : Utopia and Dystopia on the Parisian Boulevards. - Field, Amanda J. (Andrews UK, 2015)
Alone in the Crowd discusses the identity of nineteenth-century Paris, one of the most widely imaged cities in the modern world, whose most enduring attribute is that of a city of spectacle - a city of the pleasure of looking and being looked at simultaneously. Did Haussmann's re-figuring of the city, with its unrelenting straight boulevards, stirring vistas and uniform buildings, create a 'mass produced' image of Paris? If so, who benefited - and who lost out - in the construction of this new identity? Did the boulevards represent dystopia as well as utopia?